EsrE-A yigP Locus-Encoded Transcript-Is a 3′ UTR sRNA Involved in the Respiratory Chain of E. coli - Xia, Hui; Yang, Xichen; Tang, Qiongwei; Ye, Jiang; Wu, Haizhen; Zhang, Huizhan (Frontiers in Microbiology, 2017)
The yigP locus is widely conserved among γ-proteobacteria. Mutation of the yigP locus impacts aerobic growth of Gram-negative bacteria. However, the underlying mechanism of how the yigP locus influences aerobic growth remains largely unknown. Here, we demonstrated that the yigP locus in Escherichia coli encodes two transcripts; the mRNA of ubiquinone biosynthesis protein, UbiJ, and the 3’ untranslated region (UTR) small regulatory RNA (sRNA), EsrE. EsrE is an independent transcript that is transcribed using an internal promoter of the yigP locus. Surprisingly, we found that both the EsrE sRNA and UbiJ protein were required for Q8 biosynthesis, and were sufficient to rescue the growth defect ascribed to deletion of the yigP locus. Moreover, our data showed that EsrE targeted multiple mRNAs involved in several cellular processes including murein biosynthesis and the tricarboxylic acid (TCA) cycle. Among these targets, sdhD mRNA that encodes one subunit of succinate dehydrogenase (SDH), was significantly activated. Our findings provided an insight into the important function of EsrE in bacterial adaptation to various environments, as well as coordinating different aspects of bacterial physiology.